Effects of intermittent fasting on metabolism in men - Azevedo,Fernanda Reis de (2013)
This review analyzes the available literature on the impact of intermittent fasting (IF), a nutritional intervention, on different aspects of metabolism. The epidemic of metabolic disturbances, such as obesity, metabolic syndrome (MS), and diabetes mellitus type 2 has led to an increase in the prevalence of cardiovascular diseases, and affected patients might significantly benefit from modifications in nutritional habits. Recent experimental studies have elucidated some of the metabolic mechanisms involved with IF. Animal models have shown positive changes in glucose (lower plasma glucose and insulin levels) and in lipid metabolism (reduced visceral fat tissue and increased plasma adiponectin level), and an increased resistance to stress. Despite the limited number of samples studied, positive results have been reported on the impact of IF for human health. IF is reported to improve the lipid profile; to decrease inflammatory responses, reflected by changes in serum adipokine levels; and to change the expression of genes related to inflammatory response and other factors. Studies on obese individuals have shown that patient compliance was greater for IF than other traditional nutritional approaches (calorie restriction), and IF was found to be associated with low oxidative stress. Recent reports suggest that IF exerts a positive impact on the metabolic derangements commonly associated with cardiovascular diseases, and that it may be a viable and accessible intervention for most individuals. Therefore, further clinical studies are essential to test the effectiveness of IF in preventing and controlling metabolic and cardiovascular diseases.